A versatile low-resistance ohmic contact process with ohmic recess and low-temperature annealing for GaN HEMTs. (21st August 2018) - Lin, Yen-Ku; Bergsten, Johan; Leong, Hector; Malmros, Anna; Chen, Jr-Tai; Chen, Ding-Yuan; Kordina, Olof; Zirath, Herbert; Chang, Edward Yi; Rorsman, Niklas
Abstract: Deeply recessed ohmic contacts for GaN-based high electron mobility transistors (HEMTs) are demonstrated. It is shown that low-resistance ohmic contacts can be achieved with recessing beyond the AlGaN Schottky barrier where the ohmic contacts are formed on the sidewall of the recess. This makes the process versatile and relatively insensitive to the exact recess depth. The ohmic contact is based on a gold-free metallization scheme consisting of a Ta/Al/Ta metal stack requiring a low-temperature annealing. Important parameters for this type of ohmic contact process include the metal coverage, slope of the etched sidewall, bottom Ta-layer thickness, as well as annealing temperature and duration. The optimized contact resistance is as low as 0.24 Ω mm after annealing at 575 °C. Moreover, this sidewall contact approach was successfully implemented on different epitaxial heterostructures with different AlGaN barrier thickness as well as with and without AlN exclusion layer. All the samples exhibited excellent contact resistances in a wide range of recess depths. The Ta-based, sidewall ohmic contact process is a promising method for forming an ohmic contact on a wide range of GaN HEMT epitaxial designs.